Kedudukan Akal dan Wahyu dalam Islam dan Fungsinya sebagai Al-Syifa’ pada Gangguan Kejiwaan - Pramono, Didik; Sultan, Lomba; Kurniati (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This article discusses the struggle for the role of reason and revelation in the treatment of mental disorders. This article attempts to find points of contact and points of difference between revelation and reason in the treatment of crazy people. This research includes qualitative type of library research. The data comes from various relevant journal and book sources. Based on this study, it is concluded that reason is the standard for someone to be given a burden/taklif or a law. People whose minds are disturbed so that they are unable to differentiate between good and bad are called mentally disturbed people. Treatment and treatment of mental disorders and illnesses can include self-control, simplicity of life, staying away from bad morals, and making reason the essence of oneself. The revelation approach can also be taken by using the Al-Qur'an as medicine.